Review paperVolumetric techniques: three-dimensional midface modeling - Macierzyńska, Arleta; Pierzchała, Ewa; Placek, Waldemar (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Aging is a complex process caused by many factors. The most important factors include exposure to UV radiation, smoking, facial muscle movement, gravity, loss and displacement of fat and bone resorption. As a symptom of aging, face loses elasticity, volume and cheerful look. While changing face proportions, the dominant part of a face is its bottom instead of the mid part. The use of three-dimensional face modelling techniques, particularly the mid-face – tear through and cheeks, restores the skin firmness, volume and healthy look. For this purpose the hyaluronic acid is used, calcium hydroxyapatite, and L-polylactic acid fillers. Volumetric techniques require precision and proper selection of the filling agent to give a sense of satisfaction to both the patient and the doctor.